Use of anonymous social media accounts as self-disclosure media for Generation Z on postmodernism - Syafruddin Pohan; M Akbar Hasyim Lbs (Universitas Bunda Mulia, 2022)
This paper aims to see how anonymous social media accounts are used as a medium of self-disclosure and by adolescents in the era of postmodernism. This study uses a constructivist paradigm with a descriptive method through a qualitative approach. Data collection is done by using library research techniques. Data sources come from relevant literature, such as books, journals, or scientific articles. Data analysis was carried out by identifying problems that occurred related to the research topic, then analyzed with a postmodernism perspective to reveal social realities that occurred in adolescents in the use of anonymous social media from the standpoint of Jean Baudrillard's simulacra theory and conclusions were drawn. The results of the study show that both the positive and negative impacts of using anonymous social media accounts, in the view of postmodernism, put forward a very subjective truth. In the context of adolescent self-disclosure, limits will be determined by personal will, and the benefits of self-disclosure refer to individual satisfaction. Adolescents are forced to enter into hyperreality conditions that are intended to deceive adolescents in a subtle way, namely deceiving and believing that the simulation is the real reality so that adolescents become dependent on the simulation and possessive.